ACROSTERNUM HEEGERI (HETEROPTERA: PENTATOMIDAE) IN SERBIA (Acta Entomologica Serbica, 2020)
The species Acrosternum heegeri Fieber, 1861 is a well-known member of the Mediterranean fauna in Europe and until recently was not recorded outside its natural range. In recent years, the presence of stable populations of the species in Budapest has been confirmed, and the first findings on the territory of Serbia are from 2013, when several overwintering adults were found under the bark of deciduous trees in Novi Sad. Since 2017, active individuals have been recorded throughout the season, for now mainly from the area of ​​Vojvodina. This bug is probably conquering new territories by transporting people and goods, but we assume that climate change is also responsible for establishing stable populations in new environments. The paper presents the findings of the species A. heegeri in Serbia, which were taken from the Alciphron database on insects in Serbia. A. heegeri is a polyphagous herbivore and has the status of an economically significant species in the Middle East because it causes damage in pistachio plantations.